Birth order, personality, and tattoos: A pre-registered empirical test of the 'born to rebel' hypothesis. (April 2023) - Richards, Gareth; Newman, Miles; Butler, Amy; Lechler-Lombardi, Julia; Osu, Tinisha; Krzych-Miłkowska, Karolina; Galbarczyk, Andrzej
Abstract: Sulloway's 'born to rebel' hypothesis posits that later-borns develop personality characteristics which diverge from the status quo. Considering inconsistencies in the birth order literature as well as theoretical and methodological criticisms levied against this theory, we tested predictions derived from it using a sample of N  = 2011 participants from the UK and Poland. We predicted later-borns would more likely have tattoos, and that this would be mediated by openness, risk-taking, sensation-seeking, and need for uniqueness. Tattooed individuals had higher risk-taking, sensation-seeking, and need for uniqueness, but birth order was not a predictor of having tattoos. Furthermore, although later-borns had higher risk-taking and sensation-seeking, they had lower need for uniqueness. Our results do not provide support for the 'born to rebel' hypothesis. Highlights: The 'born to rebel' hypothesis posits later-borns are more likely to diverge from the status quo. Study tests if first-borns and later-borns differ in personality and likelihood of having tattoos. First-borns and later-borns did not differ in having tattoos, or in number or visibility of tattoos. Later-borns reported higher risk-taking and sensation-seeking but lower need for uniqueness. Tattooed individuals reported higher risk-taking, sensation-seeking, and need for uniqueness.